2016
DOI: 10.1016/j.biortech.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Reprint of: Effect of fermentation parameters, elicitors and precursors on camptothecin production from the endophyte Fusarium solani

Abstract: Volumetric productivity of camptothecin from the suspension culture of the endophyte Fusarium solani was enhanced up to ∼152 fold (from 0.19μgl(-1)d(-1) to 28.9μgl(-1)d(-1)) under optimized fermentation conditions including initial pH (6.0), temperature (32°C) and agitation speed (80rpm) with (5% (v/v)) ethanol as medium component. Among various elicitors and precursors studied, tryptamine (0.5mM) as precursor and bovine serum albumin (BSA) (0.075mM) as an elicitor added on day 6 of the cultivation period resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Undeniably, endophytic Fusarium species living inside host plant tissues without causing any symptoms of disease have proven over the years an outstanding potential by producing compounds actually approved for the treatment of several diseases including cancer, malaria, oxidative stress-related diseases, and inflammatory disorders. In fact, medicines such as vinblastine and vincristine (Zhang et al 2000;Tung et al 2002;Kumar et al 2013;Ashuthosh et al 2013), podophyllotoxin (Kour et al 2008;Nadeem et al 2012), camptothecin and its analogues (Kusari et al 2009;Shweta et al 2010;Venugopalan et al 2016;Ran et al 2017), taxol (Li et al 2009;Gurudatt et al 2010;Elavarasi et al 2012;Xiong et al 2013), rohitukine (Kumara et al 2014), ginkgolide B (Cui et al 2012), quinine and cinchonidine (Hidayat et al 2015) have been reported as products of in vitro fermentation of several Fusarium species. These findings have been over the years a catalyst to continue the exploration of this genus with a goal to sustain the production of such pharmacologically important drugs via microbial fermentation but have also encouraged the investigation of these species as sources of a potential drug candidates against diverse diseases.…”
Section: Medicines From Fusarium Speciesmentioning
confidence: 99%
“…Undeniably, endophytic Fusarium species living inside host plant tissues without causing any symptoms of disease have proven over the years an outstanding potential by producing compounds actually approved for the treatment of several diseases including cancer, malaria, oxidative stress-related diseases, and inflammatory disorders. In fact, medicines such as vinblastine and vincristine (Zhang et al 2000;Tung et al 2002;Kumar et al 2013;Ashuthosh et al 2013), podophyllotoxin (Kour et al 2008;Nadeem et al 2012), camptothecin and its analogues (Kusari et al 2009;Shweta et al 2010;Venugopalan et al 2016;Ran et al 2017), taxol (Li et al 2009;Gurudatt et al 2010;Elavarasi et al 2012;Xiong et al 2013), rohitukine (Kumara et al 2014), ginkgolide B (Cui et al 2012), quinine and cinchonidine (Hidayat et al 2015) have been reported as products of in vitro fermentation of several Fusarium species. These findings have been over the years a catalyst to continue the exploration of this genus with a goal to sustain the production of such pharmacologically important drugs via microbial fermentation but have also encouraged the investigation of these species as sources of a potential drug candidates against diverse diseases.…”
Section: Medicines From Fusarium Speciesmentioning
confidence: 99%
“…Lee et al [ 64 ] tested this ethanol extract in a xenograft mouse model and found a significant inhibition of tumor growth and a reduction in mouse mortality. On the other hand, the genus Fusarium was studied in four articles, showing active functional extracts against CaCo-2, HCT-116, and HCT-8 cells (IC 50 between 0.3779–98.68 μg/mL) [ 25 , 66 , 67 , 68 ]. In one article, standard camptothecin and camptothecin crude extract were isolated and tested against CaCo-2 cells, resulting in IC 50 values of 2.41 and 0.291 μM, respectively [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…By optimizing the conditions of limonin synthesis, the limonin yield could be significantly improved. In addition, it was necessary to determine the optimal conditions for microorganism‐based limonin synthesis .…”
Section: Discussionmentioning
confidence: 99%
“…Endophytes can produce secondary metabolites that have a similar or the same biological activity as those of the host. To date, a great number of natural products possessing biological activities have been isolated from endophytes, such as paclitaxel (also known as Taxol) , podophyllotoxin , homoharringtonine , camptothecin and its structural analogs , epipolythiodiketopiperazines , and azadirachtin. However, endophytes that can produce limonin have not been reported.…”
Section: Introductionmentioning
confidence: 99%